ADMINISTRATIVE INFORMATION SYSTEM DESIGN SERVICES (COSTUMER SERVICE) ON TWO WHEELS MOTOR VEHICLES AUTOMOTIVE SERVICES USING VISUAL BASIC 6.0 AND DATABASE MYSQL - Muhammad Oetomo Rizky Irwanto; Aqwam Rosadi Kardian, Skom.,MM. (Jurnal Sistem Informasi, 2010)
Along with the rapid development era, the more problems faced by humans. Thenecessity to solve a problem quickly, accurately and efficiently is very necessary.Therefore science and information technology is always developed to make it happen.In this study, the authors make a computerized system to process service administrationservices motorcycles in the automotive services using Visual Basic 6.0 programminglanguage and MySQL database.Programs that exist in this application is comprised of the main menudisplay the data menu, the menu of transactions, reports menu. Where there are datamenu sub menu of customer data input, data, mechanical data and data types of service.Transaction menu there is a sub menu of the transaction. While there are reports of submenu print menu and save the receipts, customer data printing sub menu and sub menu ofprint transaction data. Where is the menu of this report is used to display andprint reports.Application of this system aims to replace the manual system with a system that has beencomputerized, with the expectation it can make a way companies work better, especiallyin the administration.